2020
DOI: 10.3928/19404921-20190930-03
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Community-Dwelling Older Adults Living Alone in China: Association of Social Support Network and Functional Ability

Abstract: Older adults who live alone are more likely to experience depressive symptoms compared to those who live with others. The current study aimed to investigate the prevalence of depression and identify its associated factors among community-dwelling older adults living alone in China. A cross-sectional questionnaire survey was conducted with a total of 172 older adults living alone in Nanjing city, Jiangsu province of mainland China. The prevalence of depression among this group of Chinese older adults was 18.6%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The cutoff score over five or six points is suggestive of depression and a score over 10 points is almost always depression [12]. Depressive symptoms can restrict older adults' daily functional abilities and psychosocial factors such as social isolation, loneliness, and living alone in older adults [13][14][15]. A previous study found that increased risk of depressive symptoms is associated with lack of social contact [16] and poor social relationships [17].…”
Section: Introductionmentioning
confidence: 99%
“…The cutoff score over five or six points is suggestive of depression and a score over 10 points is almost always depression [12]. Depressive symptoms can restrict older adults' daily functional abilities and psychosocial factors such as social isolation, loneliness, and living alone in older adults [13][14][15]. A previous study found that increased risk of depressive symptoms is associated with lack of social contact [16] and poor social relationships [17].…”
Section: Introductionmentioning
confidence: 99%
“…Social networks are concepts related to the formal structure of social relations such as size, composition, frequency of contact, and boundaries [ 33 ]. Some social networks decrease depression, using the Lubben social network scale [ 34 , 35 , 36 ] and the framework of the World Bank’s Social Capital Assessment Tool [ 29 ]. Others decrease depression scores using the Revised Lubben Social Network Scale [ 37 , 38 , 39 ], the Chinese version of the Intergenerational Relationship Scale [ 20 ], the Social Support Scale [ 40 ], the version of portions of the social networks [ 25 ], network structure and social network function [ 19 ], network size and social interaction [ 30 , 41 , 42 ], and number of visitors per week [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…The severity of geriatric depression might vary dramatically depending on living arrangements (14). Previous studies have shown the relationship between living arrangements and depression, but the conclusions were not consistent (5,(15)(16)(17). A cross-sectional study from South Korea reported that living without a spouse in their family and living alone were most strongly associated with depressive symptoms (15).…”
Section: Introductionmentioning
confidence: 93%